Cyclooxygenase-Inhibiting Platinum(IV) Prodrugs with Potent Anticancer Activity - Aleen Khoury; Jennette A. Sakoff; Jayne Gilbert; Kieran F. Scott; Shawan Karan; Christopher P. Gordon; Janice R. Aldrich-Wright (Pharmaceutics, 2022)
Platinum(IV) prodrugs of the [Pt(PL)(AL)(COXi)(OH)]2+ type scaffold (where PL is 1,10-phenanthroline or 5,6-dimethyl-1,10-phenanthroline, AL is 1S,2S-diaminocyclohexane, and COXi is a COX inhibitor, either indomethacin or aspirin) were synthesised and characterised, and their biological activity was explored. MTT assays showed that these complexes exhibit outstanding activity against a range of cancer cell lines, and nanomolar activities were observed. The most potent complex, 4, exhibited a GI50 of 3 nM in the Du145 prostate cancer cell line and was observed to display a 1614-fold increased activity against the HT29 colon cancer cell line relative to cisplatin. ICP-MS studies showed a linear correlation between increased cellular accumulation of the complexes and increased cytotoxicity, while an enzyme immunoassay showed that 1 and 2 inhibited COX-2 at 14 and 1.4 µM, respectively, which is comparable to the inhibition exhibited by indomethacin. These results suggest that while the cytotoxicity of prodrugs 1–4 was influenced by cellular uptake, it was not entirely dependent on either COX inhibition or lipophilicity.